Better off breathing: an explanation for the seemingly detrimental impact of aerobic respiration on Zymomonas mobilis - James B. McKinlay (mBio, 2024)
ABSTRACTThe bacterium Zymomonas mobilis is best known for fermentatively producing more ethanol than yeast. However, Z. mobilis has also puzzled researchers for decades with the counterintuitive observation that disrupting aerobic respiration benefits aerobic growth, implying that fermentation remains favorable. Retention of detrimental respiration genes seemed to defy natural selection. New findings by Felczak et al. help clarify the importance of respiration for Z. mobilis and the factors that led to the confusing prior results (M. M. Felczak, M. P. Bernard, and M. A. TerAvest, 2023, mBio 14:e02043-23, https://doi.org/10.1128/mbio.02043-23). The team overcame redundancy from multiple genome copies to delete what turned out to be a key terminal oxidase. Unlike previous studies, wherein mutants exhibited low respiration rates and had improved aerobic growth, this mutant was incapable of respiration and had poor aerobic growth. Thus, respiration is important but surprisingly exceeds what is optimal under lab conditions. Respiration likely protects against toxic effects of oxygen, ensuring retention of respiration genes in the Z. mobilis genome.